The challenge of creative tourism - Richards, Greg (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2016)
Creativity is both the glue that binds together the fundamental building blocks of tourism and also the lubricant that makes the tourism system evolve into new dimensions. In this paper, the authors attempt to show how creativity is vital to our understanding of tourism. In particular, it is demonstrated how even traditionally ‘given’ tourism products like culture and nature are not accepted passively by tourists: creative tourists actively engage in the co-production of their natural-cultural experiences as tourists. For ‘the creative class’, authenticity is in the co-created experiences; it is not something residing inherently in the objects of consumption. However, for the tourism system to remain sustainable, the need for change in creativity should be tempered with a corresponding need for continuity. Successful tourism enterprises, thus, embody a dynamic equilibrium between continuity and change.